Recommendations for victim survivability assessment methodology based on the Manchester Arena Bombing Inquiry - Mark Ballard; Anthony M.J. Bull; Jonathan C. Clasper; Alan E. Hepper; Emrys Kirkman; Peter F. Mahoney (Forensic Science International: Synergy)
An expert panel was assembled to report on whether either earlier or different medical treatment could have allowed any of the 22 fatalities of the Manchester Arena Bomb to survive. The aim of this paper is to report on the methodology used by the panel, and to make recommendations for future forensic analyses of explosive events.The panel comprised individuals with a broad range of expertise who received relevant materials from the Inquiry Solicitors. The methodology used was iterative and comprehensive with the panel meeting together at regular points to: sequentially review all the material; conduct detailed analyses on the material; review the outputs of the analyses; reconcile and address any inconsistencies or points of debate; strictly define the following terms: unsurvivable, unlikely to be survivable, and potentially survivable; and report to the Inquiry. A second level of iteration was overlayed on this due to: early reporting being requested by the Solicitors to the Inquiry prior to all information being provided; and the expert panel conclusions being contested by the family of one of the casualties and the medical experts appointed by their legal teams, resulting in further analyses being conducted by the panel. The following detailed analyses were conducted for each fatality: injury scoring; injury visualisation and mapping; forensic three-dimensional post-mortem CT scan analysis; ballistic injury analysis; blood loss analysis; tourniquet use; blast lung injury; and categorisation and survivability.The panel concluded that 21 individuals suffered unsurvivable injuries and one suffered potentially survivable injuries. In order to complete their tasking, the panel found that: no one piece of evidence and expertise on its own was sufficient; post-mortem CT imaging to assess anatomical damage and body worn video to analyse physiological response were key; and lack of detailed information on survivors hindered the panel's work.The clarity of outputs provided by the panel with only the conclusion regarding one of the fatalities being contested highlights the robustness of this panel approach. The following recommendations are made that, in addition to the information that was provided to the panel during this Inquiry, the following information be provided during any future forensic analyses of explosive events: the location of survivors, and uninjured; medical records of the survivors; the three-dimensional plans of the location; structural damage records; and building records and construction technique.